Estimasi Maximum Unsupported Span dan Stand-Up Time pada Bukaan Bawah Tanah Menggunakan Metode Q-System Berdasarkan Pemodelan Spasial Kualitas Massa Batuan - Muhammad Hudiya Atharrahman; Zufialdi Zakaria (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2026)
This study aims to estimate the Maximum Unsupported Span (MUS) and stand-up time of underground openings in the X area, PT Y, using the Q-system based on spatial modeling of rock mass quality. In the study area, the main geotechnical data were obtained from boreholes because the previously excavated underground openings were flooded and had high carbon dioxide concentrations, preventing direct underground geotechnical mapping. Q-system parameters derived from borehole logging were spatially modeled using linear interpolation to represent the distribution of rock mass quality within the underground opening model. The modeled Q values were then used to empirically estimate MUS, while stand-up time was estimated by converting Q values into RMR using Bieniawski’s empirical correlation and then comparing the results with the relationship between opening span and unsupported stability time. The results indicate that the rock mass quality in the study area generally falls within the moderate to good classes, with spatial variation in several opening segments. MUS values show a positive relationship with Q values, where higher Q values correspond to higher MUS values. The stand-up time estimation indicates that, within the same rock mass class, openings with smaller spans tend to have longer stability durations than those with larger spans. These results can be used as an initial reference for underground opening development planning, although they still need to be adjusted to actual field conditions.